1989
DOI: 10.1111/j.1365-2796.1989.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypocalciuric hypercalcaemia: a study of four kindreds

Abstract: Four kindreds with hereditary hypercalcaemia have been investigated. Thirty-seven of 72 subjects examined had hypercalcaemia with an autosomal dominant pattern of inheritance. Hypercalcaemic patients had total serum calcium of 2.91 +/- 0.12 mmol l-1. Serum parathyroid hormone (PTH) was normal while daily urinary calcium excretion was subnormal (below 2.5 mmol) in 45%. Comparison with an age-matched group of patients with primary hyperparathyroidism gave a small overlap regarding serum human PTH, urinary calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The extra measured parameter, serum calcium, rarely exceeds 3.2 mmol/L in FBHH. 1,6,7,9,12,13,18,29,43 In two early extensive reviews, 3,15 occasional values up to 3.5 mmol/L were reported. Therefore, serum calcium may have higher values in PHPT than in FBHH 6,7 and result in a lower calcium:creatinine clearance ratio in some cases, and thus a greater overlap in results.…”
Section: Laboratory Features Of Fbhhmentioning
confidence: 99%
See 1 more Smart Citation
“…The extra measured parameter, serum calcium, rarely exceeds 3.2 mmol/L in FBHH. 1,6,7,9,12,13,18,29,43 In two early extensive reviews, 3,15 occasional values up to 3.5 mmol/L were reported. Therefore, serum calcium may have higher values in PHPT than in FBHH 6,7 and result in a lower calcium:creatinine clearance ratio in some cases, and thus a greater overlap in results.…”
Section: Laboratory Features Of Fbhhmentioning
confidence: 99%
“…The numbers of subjects from each study, with the range and median of the six most commonly studied biochemical parameters overall, are summarized in Table 3. Of the 10 studies, three were of a single large kindred, 1,13,18 ¢ve consisted of series of cases of FBHH and PHPT collected separately over unspeci¢ed time periods, 3,9,12,42,43 and two were prospective studies of unselected cases of hypercalcaemia over a 3-year period in the same hospital. 6,7 A spreadsheet containing the original data from these studies is available at www.acb.org.uk/annclinbiochem/ webwise/ADHHClinBiochem.xls and www.acb.org.uk/ annclinbiochem/webwise/FBHHCalciumdata.xls Table 4 summarizes data for the six most commonly measured biochemical parameters.…”
Section: Laboratory Features Of Fbhhmentioning
confidence: 99%
“…Marx et al [2] identified familial hypercalcemia in 13 out of 25 patients (52%) with parathyroid hyperplasia; but only 2 patients out of the 13 (13%) with familial hypercalcemia Sporadic reports of FHH kindreds appeared from France [20][21][22], Spain [23], Norway [24], Sweden [25], Denmark [26,27], the Netherlands [16,28], Italy [29], Switzerland [30], and Japan [31][32][33][34]. This limited data suggests that FHH is prevalent in many parts of the world, but no specific conclusions can be drawn about its ethnic distribution.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by asymptomatic and usually uncomplicated lifelong hypercalcemia. [1][2][3][31][32][33][34]37,38 It was estimated that FHH accounted for about 9% of failed parathyroidectomies in patients presenting to the NIH in the 1970s, 39 the proportion was 23% in a more recent series from Denmark. Longevity is normal as demonstrated in large studies from the National Institutes of Health, the Mayo Clinic, and others.…”
Section: Key Characteristicsmentioning
confidence: 99%
“…43,44 Furthermore, there appears to be no increased incidence of fractures in FHH, and the skeletons of these patients are normal by histomorphometric, radiologic, and densitometry criteria. [31][32][33][34]37,38,43,[45][46][47] Unfortunately, FHH does not provide immunity against age-related bone loss; elderly patients with FHH may have osteoporosis indistinguishable from that expected for their age.…”
Section: Symptoms and Complicationsmentioning
confidence: 99%